Mental health in young mothers, single mothers and their children - Agnafors, Sara; Bladh, Marie; Svedin, Carl Göran; Sydsjö, Gunilla (BMC psychiatry, 2019)
Background Parenthood is a life transition that can be especially demanding for vulnerable individuals. Young maternal age and maternal single status have been reported to increase the risk for adverse outcomes for both mother and child. The aim of this study was to investigate the effect of young maternal age and maternal single status on maternal and child mental health and child development at age 3. Methods A birth-cohort of 1723 mothers and their children were followed from birth to age 3. Sixty-one mothers (3.5%) were age 20 or younger, and 65 (4.0%) reported single status at childbirth. The mothers filled out standardized instruments and medical information was retrieved from the standardized clinical assessment of the children at Child Welfare Centers, (CWC). Results Young maternal age was associated with symptoms of postpartum depression whereas single status was not. Young mothers were more prone to report internalizing and externalizing problems in their children, while there was no association between single status and child behavioral problems. No differences were seen on child development (CWC scores). School drop-out was, however, a more influential factor on depressive symptoms postpartum than maternal age. Conclusion Young mothers are at increased risk for symptoms of postpartum depression which indicates the need for attention in pre- and postnatal health care programs. Single mothers and their children were not found to be at increased risk for adverse outcomes. The importance of schooling was demonstrated, indicating the need for societal support to encourage adolescents to remain in school.